2001
DOI: 10.1101/gr.169601
|View full text |Cite
|
Sign up to set email alerts
|

A Bacterial Artificial Chromosome Library for Sequencing the Complete Human Genome

Abstract: A 30-fold redundant human bacterial artificial chromosome (BAC) library with a large average insert size (178 kb) has been constructed to provide the intermediate substrate for the international genome sequencing effort. The DNA was obtained from a single anonymous volunteer, whose identity was protected through a double-blind donor selection protocol. DNA fragments were generated by partial digestion with EcoRI (library segments 1–4: 24-fold) and MboI (segment 5: sixfold) and cloned into the pBACe3.6 and pTAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
236
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(242 citation statements)
references
References 52 publications
(54 reference statements)
4
236
0
2
Order By: Relevance
“…For the two subjects with atypical deletions negative for the clinical probe, BAC probe RP11-138C22 containing the COMT primer set, was selected for FISH analysis to confirm qPCR results. The BAC originated from the RPCI library 11 of BAC clones (Osoegawa et al 2001), obtained courtesy of the Centre for Applied Genomics at the Hospital for Sick Children (Toronto, Canada). Both ends of the RP11-138C22 clone (AQ383658 and AQ383661) are free of repeats and map with 100% identity only to cytoband 22q11.21 in the interval 18253741-18429812.…”
Section: Fish Studiesmentioning
confidence: 99%
“…For the two subjects with atypical deletions negative for the clinical probe, BAC probe RP11-138C22 containing the COMT primer set, was selected for FISH analysis to confirm qPCR results. The BAC originated from the RPCI library 11 of BAC clones (Osoegawa et al 2001), obtained courtesy of the Centre for Applied Genomics at the Hospital for Sick Children (Toronto, Canada). Both ends of the RP11-138C22 clone (AQ383658 and AQ383661) are free of repeats and map with 100% identity only to cytoband 22q11.21 in the interval 18253741-18429812.…”
Section: Fish Studiesmentioning
confidence: 99%
“…18,19 Detailed protocols are available at the MPI webpage (http://www.molgen.mpg.de/~abt_rop/molecular_ cytogenetics/ProtocolsEntry.html). The patient's DNA and a pooled reference DNA were fluorescently labelled with Cy5 and Cy3, respectively, using the Bioprime Array CGH labelling kit (Invitrogen, Carlsbad, CA, USA).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…AC010650) and 11-190D6 (GenBank accession no. AC009044) from the RPCI-11 library (Osoegawa et al, 2001) are included in the map based on sequence identity to the probes indicated with dashed lines. Filled circles indicate the T7 end of the PAC clones as determined by the hybridization with Sp6 and T7 oligonucleotides.…”
Section: Expression Of Wwox Mrnas In Human Breast Tumorsmentioning
confidence: 99%